Investigation of existing car parking standard in Kangar town / Nur Illliana Md Lazim - Md Lazim, Nur Illliana (2019)
Nowadays, people keep busy to own their parallel towards in developing countries. As we can see, Kangar Town also busy with people to get education and services. Indirectly, there will be a major issue in parking problems. One of the problems is the limitation of parking space which is require drivers to take a long time to find the available parking.Other than that, small parking size also one of the problem. This is because drivers will face difficulties in getting out of their car. By refer to my research questionnaire, people complaint that their car will scratch to other car when parked side by side. Since the dimension of car parking in Malaysia used the standard dimensions, all states should follow the guideline that has been stated by Jabatan Kerja Raya (JKR). Jabatan Perancangan Bandar dan Desa (JPBD) Semenanjimg Malaysia also has their owned guide to be refered in this study. The purpose of this study is to investigate the existing parking size and its dimension in Kangar town. In this study. Static Global Positioning System (GPS) method is used to obtain the coordinate of the parking lot. It is used as a control method. Total station also used to collect the data. Meanwhile, for processing data, AutoCAD software is used to show the different size of both designs to analyze patterns and dimension of existing parking in Kangar town. In a nut shell, the final result is obtained by comparing the existing map car parking layout with the proposed car parking layout.The result shows that the existing parking in Kangar are not hundred percent (100%) followed by the guidelines for all types of parking lot. Therefore, the government, private agencies or responsible parties need to solve the problem about car parking. Even this is not a big problem but causing dissatisfaction or comfort to the users.